Study of endophytic fungi of Ipomoea pes-caprae reveals the superiority of in situ plant conservation over ex situ conservation from a mycological view - Yu-Hung Yeh; Roland Kirschner (Scientific Reports)
Abstract In nature conservation, ex situ and in situ conservation strategies are discussed for protecting endangered species of plants and animals. However, the impacts of these strategies on the microbes associated with these species are rarely considered. In our study, we chose the endophytic fungi of the pantropical creeping plant Ipomoea pes-caprae as representative coastal plant in two natural coastal populations and two botanical gardens in Taiwan as collection sites in order to investigate the potential effect of ex situ plantation on the biodiversity of microbes intimately associated with this plant. In a culture-dependent approach, endophytic fungi were isolated under axenic conditions and identified to species, genus, or higher taxonomic ranks with DNA barcodes and morphology. In addition to yielding ca. 800 strains and over 100 morphospecies, a principal component analysis (PCA) of the distribution of the dominant fungal species showed clear differences in the composition of endophytic fungal species depending on the sampling sites. We conclude that the endophytic fungi from the original site are replaced by other species in the ex situ plantations. Due to the limitations of ex situ conservation of microbes and from a mycological and microbial perspective, in situ conservation should outweigh ex situ approaches.